Pengaruh Kepemimpinan Kepala Sekolah dan Iklim Komunikasi Organisasi Terhadap Kinerja Guru di SMA Sekecamatan Cengal Kabupaten Ogan Komering Ilir - Sofwan, Muhammad; Putra, Alhadi Yan; Rohana, Rohana (CV. Ulil Albab Corp, 2025)
This study was conducted to describe and analyze the influence of principal leadership on Teacher Performance, the influence of Organizational Communication Climate on Teacher Performance, the influence of Principal Leadership and Organizational Communication Climate together on Teacher Performance in State Senior High Schools throughout Cengal District. Data were obtained using questionnaires, documentation and observation methods which were then analyzed using simple linear regression analysis techniques and multiple linear regression. The results of the study concluded that 1) there is an influence of principal leadership on teacher performance in State Senior High Schools throughout Cengal District. The contribution of the principal leadership variable to teacher performance based on the R value is 67.8%, while the influence given by the principal leadership variable to teacher performance is 46.0%, 2) there is an influence of organizational communication climate on teacher performance in State Senior High Schools throughout Cengal District. The contribution of organizational communication climate variables to teacher performance based on the R value is 68.2%, while the influence given by the organizational communication climate variable to teacher performance is 46.5%, and 3) there is an influence of principal leadership and organizational communication climate together on teacher performance in State Senior High Schools in Cengal District. The amount of contribution of the principal leadership and organizational communication climate variables to teacher performance based on the R value is 73.3%, while the influence given by the principal leadership and organizational communication climate variables to teacher performance is 53.7%.